No advantage of antimicrobial prophylaxis in AML/MDS/CMML patients treated with azacitidine—a prospective multicenter study by the Polish Adult Leukemia Group - Mądry, Krzysztof; Lis, Karol; Sienkiewicz, Elzbieta; Drozd-Sokołowska, Joanna; Biecek, Przemysław; Sośnia, Oktawia; Gołos, Aleksandra; Olszewska-Szopa, Magdalena; Obara, Agata; Walkowiak, Zuzanna; Ściesińska, Joanna; Subocz, Edyta; et al. (Frontiers in Oncology, 2024)
Infections represent one of the most frequent causes of death of higher-risk MDS patients, as reported previously also by our group. Azacitidine Infection Risk Model (AIR), based on red blood cell (RBC) transfusion dependency, neutropenia <0.8×10⁹/L, platelet count <50×10⁹/L, albumin <35g/L, and ECOG performance status ≥2 has been proposed based on the retrospective data to estimate the risk of infection in azacitidine treated patients. The current prospective study aimed to identify factors predisposing to infection, validate the AIR score, and assess the impact of antimicrobial prophylaxis on the outcome of azacitidine-treated MDS/AML and CMML patients. We collected data on 307 patients, 57.6 % males, treated with azacitidine: AML (37.8%), MDS (55.0%), and CMML (7.1%). The median age at azacitidine treatment commencement was 71 (range, 18-95) years. 200 (65%) patients were assigned to higher risk AIR group. Antibacterial, antifungal, and antiviral prophylaxis was used in 66.0%, 29.3%, and 25.7% of patients, respectively. In total, 169 infectious episodes (IE) were recorded in 118 (38.4%) patients within the first three azacitidine cycles. In a multivariate analysis ECOG status, RBC transfusion dependency, IPSS-R score, and CRP concentration were statistically significant for infection development (p<0.05). The occurrence of infection within the first three azacitidine cycles was significantly higher in the higher risk AIR group -47.0% than in lower risk 22.4% (odds ratio (OR) 3.06; 95% CI 1.82-5.30, p< 0.05). Administration of antimicrobial prophylaxis did not have a significant impact on all-infection occurrence in multivariate analysis: antibacterial prophylaxis (OR 0.93; 0.41-2.05, p=0.87), antifungal OR 1.24 (0.54-2.85) (p=0.59), antiviral OR 1.24 (0.53-2.82) (p=0.60). Conclusions: The AIR Model effectively discriminates infection risk patients during azacitidine treatment. Antimicrobial prophylaxis does not decrease the infection rate.